2011
DOI: 10.1093/qjmed/hcr107
|View full text |Cite
|
Sign up to set email alerts
|

Update on anti-coagulation in atrial fibrillation

Abstract: Atrial fibrillation (AF), the most common clinically relevant arrhythmia, affects 2.2 million individuals in the USA and 4.5 million in Europe, resulting in significant morbidity and mortality. Pharmacotherapy aimed at controlling both heart rate and rhythm is employed to relieve AF symptoms, though debate continues about which approach is preferable. AF prevalence rises with age from 0.4% to 1% in the general population to 11% in those aged >70 years. AF is associated with a pro-thrombotic state and other com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The importance of anticoagulation cannot be understated, as shown in many studies, the ability of warfarin use to save up to 26% of lives and prevent 67% of strokes in patients with atrial fi brillation, adding to all the risks for women as mentioned [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of anticoagulation cannot be understated, as shown in many studies, the ability of warfarin use to save up to 26% of lives and prevent 67% of strokes in patients with atrial fi brillation, adding to all the risks for women as mentioned [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…As the population ages, the incidence of AF is projected to increase by 2.5 fold in the next 50 years [2]. It is responsible for one-third of the hospitalizations for cardiac rhythm disturbances and is associated with significant morbidity and mortality, including a 4-fold to 5-fold increased risk of stroke and 3-fold increased risk of heart failure, resulting in significant effects on quality of life (QoL) [3]. Stroke is the third leading cause of death and the principal cause of serious, long-term disability in the United States, therefore exerting a high socioeconomic burden [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additional indications include the prophylaxis of recurrent thromboembolic events in individuals with venous thromboembolism and in those with prosthetic mechanical valves. Using the CHADS 2 (Congestive heart failure, Hypertension, Aged ≥75, Diabetes mellitus, Stroke or transient ischemic attack) score in treating elderly adults with atrial fibrillation has shown that they benefit from oral anticoagulant treatment for the prevention of ischemic cerebrovascular events . The benefits of oral anticoagulant treatment must always be weighed against the risk of major bleeding, especially in elderly adults .…”
mentioning
confidence: 99%
“…It also requires regular INR tests and a dedicated family physician. In clinical practice, individuals have been shown to remain within the therapeutic range for less than 45% of the time . The recommended INR for most indications, such as atrial fibrillation and venous thromboembolism, is 2 to 3.…”
mentioning
confidence: 99%